2019
DOI: 10.1590/1984-70332019v19n4c65
|View full text |Cite
|
Sign up to set email alerts
|

BRSMG Alterosa: Rice cultivar for lowland cultivation in Minas Gerais

Abstract: The lowland rice breeding program, developed in Minas Gerais state, has as basic objective to release new commercial cultivars. In this way, this program is making available a new cultivar named BRSMG Alterosa, which has as main characteristics: high grain yield, high tillering, medium cicle, diseases tolerance and high grain quality. It was recommended in 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“… The hybrid controller based on the method of Eberhart and Russell (1966) and Lin and Binns (1988) modified by Carneiro (1998) is a suitable tool to automate decision‐making in the recommendation of cultivars in breeding programmes. The results indicated that BRA 02691 is an ideal cultivar, with a high mean 5302 kg ha −1 , a 𝛽 1 equal to 1, and a high predictability of behaviour ( R2 of 80.43%). BRA 02691 was recently accredited as a new commercial cultivar, termed ‘BRSMG Alterosa’ (Soares et al, 2019). Therefore, this genotype may contribute to satisfactory results in favourable and unfavourable environments. The hybrid fuzzy controller based on the methods of Eberhart and Russell (1966) and the modified method of Lin and Binns (Carneiro, 1998) indicated that the genotypes MGI 0607‐1, BRA041230, BRA 031001, BRA 01330 and the rice cultivar ‘Ourominas’ showed general adaptability with high average grain yield suitable to be used as parents in future breeding programmes. …”
Section: Discussionmentioning
confidence: 99%
“… The hybrid controller based on the method of Eberhart and Russell (1966) and Lin and Binns (1988) modified by Carneiro (1998) is a suitable tool to automate decision‐making in the recommendation of cultivars in breeding programmes. The results indicated that BRA 02691 is an ideal cultivar, with a high mean 5302 kg ha −1 , a 𝛽 1 equal to 1, and a high predictability of behaviour ( R2 of 80.43%). BRA 02691 was recently accredited as a new commercial cultivar, termed ‘BRSMG Alterosa’ (Soares et al, 2019). Therefore, this genotype may contribute to satisfactory results in favourable and unfavourable environments. The hybrid fuzzy controller based on the methods of Eberhart and Russell (1966) and the modified method of Lin and Binns (Carneiro, 1998) indicated that the genotypes MGI 0607‐1, BRA041230, BRA 031001, BRA 01330 and the rice cultivar ‘Ourominas’ showed general adaptability with high average grain yield suitable to be used as parents in future breeding programmes. …”
Section: Discussionmentioning
confidence: 99%
“…Irrigated rice is very important in Brazil, with an annual production of about 10 Tg in 2018–2019 and represents 80% of planted area of rice in the country. Minas Gerais is the leading state in flood‐irrigated rice production in the Southeast Region and in the 2018–2019 growing season obtained a state mean yield of 6631 kg ha −1 , grown on an area of .9 thousand hectares (CONAB, 2019; Soares et al, 2019). Although, the rice area decreased in the last years, Minas Gerais had an increased production over time.…”
Section: Introductionmentioning
confidence: 99%